2016
DOI: 10.1016/j.jand.2016.06.195
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition Composition of Snacks Offered to Young Recreational Soccer Players

Abstract: Snacking behavior has changed dramatically over the past few decades, with snacking frequency reaching upwards of three times per day and comprising 27% of daily calorie intake. Research has shown that the largest food groupings from snacks are grain-based desserts, sweetened beverages, and salty snacks. Previous studies have also shown that children are influenced by their peers. Youth sports are a very popular venue for children and opportunity for physical activity, with soccer becoming one of the most popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…They analyzed the nutrient contribution of team snacks, which contained, on average, 333 ± 157 calories, 63 ± 26 g carbohydrate, 6 ± 3.5 g protein, 9 ± 4.6 g fat, 35 ± 14 g sugar, 200 ± 156 mg sodium, and 4 ± 2.1 g fiber. 14 Similarly, D’Aria and collegues 15 observed team snacks provided to children under six years of age playing soccer, comparing them to the USDA Smart Snacks in Schools nutrition standards for elementary schools. 15 Findings indicated that grain-based desserts were the most popular snack category (31.3% of snacks foods) and that sugar-sweetened beverages were the most common drinks provided (60.4% of beverages).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They analyzed the nutrient contribution of team snacks, which contained, on average, 333 ± 157 calories, 63 ± 26 g carbohydrate, 6 ± 3.5 g protein, 9 ± 4.6 g fat, 35 ± 14 g sugar, 200 ± 156 mg sodium, and 4 ± 2.1 g fiber. 14 Similarly, D’Aria and collegues 15 observed team snacks provided to children under six years of age playing soccer, comparing them to the USDA Smart Snacks in Schools nutrition standards for elementary schools. 15 Findings indicated that grain-based desserts were the most popular snack category (31.3% of snacks foods) and that sugar-sweetened beverages were the most common drinks provided (60.4% of beverages).…”
Section: Introductionmentioning
confidence: 99%
“…14 Similarly, D’Aria and collegues 15 observed team snacks provided to children under six years of age playing soccer, comparing them to the USDA Smart Snacks in Schools nutrition standards for elementary schools. 15 Findings indicated that grain-based desserts were the most popular snack category (31.3% of snacks foods) and that sugar-sweetened beverages were the most common drinks provided (60.4% of beverages). Less than half of observed snacks met the USDA guidelines.…”
Section: Introductionmentioning
confidence: 99%
“…For example, one study found that 62% of families go out to eat after recreational soccer games [ 8 ] and food consumed outside the home and school settings is associated with a greater intake of noncore foods and increased caloric intake [ 9 , 10 ]. Two cross-sectional dissertation studies found that snacks brought to recreational soccer games by parents in the USA usually have between 300 and 500 calories, and snacks are typically grain-based desserts [ 11 , 12 ]. In US diets, grain-based desserts are the second largest source of food that contribute to added sugars [ 13 ].…”
Section: Introductionmentioning
confidence: 99%